PENGARUH KECERDASAN EMOSIONAL TERHADAP PRESTASI BELAJAR MAHASISWA FAKULTAS EKONOMI MANAJEMEN UNIVERSITAS BHAYANGKARA SURABAYA - Enny Istanti (Fakultas Ekonomi Universitas 45 Surabaya, 2016)
Competition world's work is getting sharply due to the era of globalization. Many examples around prove that the person who had a degree of higher education not necessarily successful actively involved in the work force. Activity students in organization very influential on the development of emotional intelligence. Independent variables in this study is that emotional intelligence consists of self-control (X1), motivation (X2), and social skills (X3). While the dependent variable is Student Learning Achievement (Y). The population in this study were students of Economics Faculty of Management Prodi class 2008, 2009 and 2010 because the students were considered to have had a GPA that shows the results of their final semester who had traveled during the study as many as 84 students. The sampling technique used in this study using proportionate Stratified Random Sampling. Data analysis techniques used in this study is the multiple linear regression. The results obtained in this study are variables Self-Control, Motivation and Social Skills simultaneous effect of Learning on Student Achievement Management Faculty of Economics, University of Surabaya Bhayangkara because FHitung value (70 708) greater Ftabel (2.72). The results also showed that Self-Control (X1), motivation (X2) and Social Skills (X3) partially significant effect on Student Achievement Study Management Faculty of Economics, University of Surabaya Bhayangkara. The results also showed that Self-Control (X1), motivation (X2) and Social Skills (X3) partially significant effect on Student Achievement Study Management Faculty of Economics, University of Surabaya Bhayangkara. Variable that has a dominant influenceon the Student Learning Achievement Management Faculty ofEconomics, University of Surabaya is Bhayangkara motivation variable (X2).